The effect of manganese chloride on gentamicin-induced nephrotoxicity in rats - Atessahin, A; Karahan, I; Yilmaz, S; Çeribasi, AO; Princci, I (Academic Press Ltd Elsevier Science Ltd, 2003)
The aim of this study was to investigate the effects of manganese chloride on gentamicin-induced nephrotoxicity in rats. Thirty-six adult Wistar Albino rats were divided into six equal groups. They were injected with gentamicin sulfate (100 mg kg(-1) per day i.p.) and manganese chloride (2 or 20 mg kg(-1) per day i.p.) and gentamicin together with manganese chloride for 6 days. The animals were killed 24 h after the last injection. Nephrotoxicity was biochemically and histopathologically evaluated. The concentrations of creatinine, urea, sodium and potassium in plasma, malondialdehyde (MDA) and reduced glutathione (GSH) levels, glutathione peroxidase (GSH-Px) and catalase (CAT) activities in kidney tissue were determined. Administration of gentamicin to rats induced a marked renal failure, characterized with a significant increase in plasma creatinine and urea concentrations. A significant increase in kidney MDA and a decrease in GSH concentrations were observed in gentamicin-treated rats. No change was observed in the activities of GSH-Px and CAT in rats treated with gentamicin alone. Administration of the low dose of manganese (Mn2+) produced amelioration in biochemical indices of nephrotoxicity in plasma and kidney tissue when compared to gentamicin group. The histological signs of renal proximal tubules followed a similar pattern. The high dose of Mn2+ (20 mg kg(-1)) caused an opposite effect on nephrotoxicity induced by gentamicin, causing exacerbation in the tubular necrosis. The results suggest that low dose of Mn2+ may have an antioxidant effect in kidneys of gentamicin administrated rats, but its high doses had no beneficial effect. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: gentamicin; manganese; lipid peroxidation; antioxidants; histopathology